Assessment of Genetic Diversity based on Agro-morphological Traits and Genic Microsatellite Markers in Wheat Cultivars - SANGEETA KUMARI; JK SHARMA; NARESH THAKUR; S LATA (Seed Research, 2026)
A set of seventeen wheat cultivars were subjected to genetic diversity analysis based on 11 morphometric traits and 20 simple sequence repeat (SSR) markers. The highest polymorphism (93.20%) depicted that the population under study is genetically diverse. Based on polymorphism exhibited by SSR markers, dendrogram was constructed using Jaccard’s similarity coefficient using UPGMA method of NTSYS-PC package (version 2.02); the genotypes were grouped into three major clusters with a genetic similarity in the range of 37- 67 per cent. Jaccard’s similarity coefficient indices were developed on the basis of the scorable banding patterns of the 17 wheat varieties using polymorphic markers. The Jaccard’s similarity coefficient values were used as input data to construct a dendrogram based on Unweighted Pair Group Method with Arithmetic Mean (UPGMA) and SAHN clustering using the computer package NTSYSpc version 2.0. Using SSR markers, first principal component explained 37.25 per cent of the total variation followed by second component explained 93 per cent variation, third component explained 83 per cent variation, fourth component explained 6.85 per cent variation and the fifth one explained 6.01 per cent variation of the data. In principal component analysis, the genotypes from the HPW and HS series were more distant, indicating that higher genetic diversity resided in them. Results of present study will be useful in understanding the wheat genetic structure and selecting diverse accessions from analysed varieties, to be exploited in a sustainable manner in future breeding programmes.